Day one postoperative MRI findings following electrode placement for deep brain stimulation: analysis of a large case series - Succop, Benjamin S.; Zamora, Carlos; Roque, Daniel Alberto; Hadar, Eldad; Kessler, Brice; Quinsey, Carolyn (Frontiers in Neurology, 2023)
Objective: The purpose of this single-institution retrospective study is to describe the rates of radiographic abnormalities, specifically entry and track microhemorrhage, pneumocephalus, hematomas, and edema, and to compare the detection of these complications between T2 gradient echo (GRE) and T2 fluid attenuated inversion recovery (FLAIR) MR sequences in day one postoperative DBS patients. The presence of susceptibility artifact in each hemisphere, the relative size of the artifact, and associations of the artifact with other radiographic abnormalities also was described. Lastly, the association of multiple passes of the stimulating microelectrode cannula with the presence of radiographic abnormalities was evaluated. Methods: 198 bilateral DBS patients were identified and had their day one postoperative MR imaging characterized by a team consisting of a trained neuroradiologist and neurosurgeon blinded to MR sequence and patient. Associations between multiple intraoperative cannula passes and susceptibility artifact with radiographic abnormalities of interest were evaluated via multiple logistic regressions with Bonferroni correction. Ad-hoc multiple logistic regression analyses evaluated the hemisphere-specific associations. Results: Overall, 115 (58%) patients showed entry microhemorrhage; 77 (39%) patients showed track microhemorrhage; 44 (22%) patients had edema; 69 (35%) patients developed pneumocephalus; and 12 (6%) patients developed intracranial hematoma. T2 GRE was better for detecting microhemorrhage (OR=14.82, p<0.0001 for entry site and OR=4.03, p<0.0001 for electrode tract hemorrhage) and pneumocephalus (OR=11.86, p<0.0001), while T2 FLAIR was better for detecting edema (OR=123.6, p<0.0001) at Bonferroni corrected significance threshold of p=.006. The relatively common prevalence of microhemorrhage and edema were respectively best visualized by T2 GRE and T2 FLAIR sequences, respectively. More passes intraoperatively had a significant association with detection of ipsilateral track microhemorrhage (OR=7.151, p<0.0001 left; OR=8.953, p<0.0001 right). Susceptibility artifact surrounding electrodes likely interfered with further detection of ipsilateral edema (OR=4.323, p=0.0025 left side only). Discussion: Day one postoperative MRI for DBS patients can detect numerous radiographic abnormalities not identifiable on CT. An interesting finding was that multiple stimulating electrode cannula passes intraoperatively is associated with microhemorrhage along the track. Lastly, electrode susceptibility artifact is a common finding that may obscure ipsilateral edema. Further study should evaluate the clinical relevance of these observations.